Perancangan Sistem Pemesanan Rumah Sakit di Kota Malang Menggunakan Ionic Framework berbasis Mobile Phone (Jurnal Ilmiah Teknologi Informasi Asia, 2017)
Hospital facility booking application is an application that is expected to facilitate the patients for the process of booking facilities provided by the hospital. Making this application is based because of the many users of smartphones and tablets. Applications are made so that patients can access information or make reservations facilities wherever and whenever. In the application there are several features that can facilitate the user in getting the ease without having to go to the hospital in the order process. The process of designing web administrators and Applications using MVC Mechanisms is a separate application development system, the main Component that builds applications such as data manipulation (Model), user interface (View), and control sections (Controller) in web applications. Implementation MVC (Model View Controller) with CodeIgniter Framework, making the system on the application becomes easier to be developed by the next developer. Application creation on smartphones is created using Ionic Framework with basic PHP, JavaScript Framework AngularJS, and Node.js. After going through the testing process that has been done, the application is made to display information in the form of polyclinic schedule as well as the name of the doctor, make reservations at the clinic provided by the hospital, bookings for inpatient, and know the amount of bills to be paid, to communication features with the home sick to get the desired information and survey results to application users show the satisfaction level of 80.13%.